X-ray structure determination a practical guide - Stout, George H.; Jensen, Lyle H. (A Wiley-Interscience publication, 1989)
The pattern of this book follows closely an actual structural determination. After some introductory material on the nature of X-rays, the diffraction process, and the internal geometry of crystals, the selection and preparation of a crystal are considered. Techniques of measuring raw X-ray data are covered, plus their reduction into a useable form. The second part of the book discusses both traditional and novel methods of solving the 'phase problem', the principal difficulty in X-ray structure determination. The third part of the book considers how to extract the most information from the data and how to evaluate its reliability. Finally there is discussion of sources of error in practice and interpretation. The volume will be of benefit to crystallographers, organic, physical and analytical chemists, and graduate students.